« La vie de tout individu ne pourrait-elle pas être une œuvre d’art ? » Considérations historiques autour de la notion foucaldienne d’« esthétique de l’existence » - Cseke, Ákos (Verbum – Analecta Neolatina, 2020)
This paper seeks to describe and understand the notion of “aesthetics of existence” in the last works of Michel Foucault by raising the following question: what is aesthetics? First, I will sketch the problem of the difficulty of defining aesthetics as a discipline, its domain, as well as the methodological questions concerning the historiography of aesthetics, taking the example of what is referred to as “medieval aesthetics”. Then, I will try to show in what sense “the aesthetics of existence” of Michel Foucault is an integral part of the history of aesthetics in the broad sense of the term (aesthetics understood as a theory of art as well as a philosophy of sensation and beauty), focusing on The Courage of Truth and, more specifically, on Foucault’s interpretation of the works of Samuel Beckett.